Isu-Isu Multikulturalisme dalam Film â€œcin(T)a-God is a Directorâ€ dalam Konteks Keindonesiaan Sekarang - Yuwono, Elisabeth Christine (Nirmana, 2011)
â€œcin(T)a â€“ GODIS A DIRECTORâ€ is a love story indie movie which is wrapped by Indonesian social issues, such as ethnic group, religion, race, and social status. This article uses qualitative based research method, which describes and explains scene by scene along with its dialogues as to situations or events and how the different views of social issues are explained in the context of multiculturalism of recent Indonesianity.